2012
DOI: 10.5539/mas.v6n2p60
|View full text |Cite
|
Sign up to set email alerts
|

Improving Solid Waste Management in Gulf Co-operation Council States: Developing Integrated Plans to Achieve Reduction in Greenhouse Gases

Abstract: Landfills are a significant source of greenhouse gases, which contribute to the process of global warming. In the region covered by the Gulf Co-operation Council (GCC), changes in consumption patterns have led to an excessive dump of municipal solid waste (MSW). Thus, it is clearly an important time to re-evaluate conventional waste management protocols in order to establish methods that not only deal with increased demand but also minimize greenhouse gas emissions and improve efficiency of resource management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…These results are in agreement with the results obtained whose found that the desirable C/N ratio ranged for ready-to-use compost from 15:1 to 20:1 and it also agreed with the result obtained by a group researcher whose found that range of C/N ratio for kitchen waste is 13-18:1 [16,17]. This also shows that aeration does not play an important role in the elemental percentage of the sample in overall compost as the tendency to rapid decomposition and continuously decrease the volume and aeration depend on high ratio of C/N.…”
Section: Estimation Of the Percentage Of Element By Ultimate Analysissupporting
confidence: 82%
“…These results are in agreement with the results obtained whose found that the desirable C/N ratio ranged for ready-to-use compost from 15:1 to 20:1 and it also agreed with the result obtained by a group researcher whose found that range of C/N ratio for kitchen waste is 13-18:1 [16,17]. This also shows that aeration does not play an important role in the elemental percentage of the sample in overall compost as the tendency to rapid decomposition and continuously decrease the volume and aeration depend on high ratio of C/N.…”
Section: Estimation Of the Percentage Of Element By Ultimate Analysissupporting
confidence: 82%
“…Despite regional aspirations for integrated waste management (IWM) development little has been done (Abou‐Elseoud ; Arif ; Al Ansari ; UNEP ). In recent years, global (Hoornweg & Bhada‐Tata ), subregional (Al Maaded et al ., ; Arif, ; Al Ansari ; Allam et al .…”
Section: Data Sourcesmentioning
confidence: 99%
“…Regional MSW emissions assessments to date have been made using the IPCC Waste Model (Bogner et al . ) with intermittent country reporting (see Annual data – UNFCCC ) and including commentary or assessments based on strategic waste hierarchy (Al Ansari ) or methane capture as a disposal treatment (Arif :33–34) and comparison of landfill, incineration and plastic recycling on global warming potential indicators (Al Maaded et al . :6).…”
Section: Data Sourcesmentioning
confidence: 99%
“…Landfills are major source of greenhouse gases, which contribute about 3.4% to 3.9% of global greenhouse gases emissions 21 . During SW decomposition, large quantities of methane and carbon dioxide are produced, and released into the atmosphere.…”
Section: Environmental Valuesmentioning
confidence: 99%
“…During SW decomposition, large quantities of methane and carbon dioxide are produced, and released into the atmosphere. Methane is 21 times more detrimental as greenhouse gases than is carbon dioxide 19,21 . The potential reduction in greenhouse gasses for processing of waste using the Mass Burn with Recycling and Mass Burn scenarios in comparison to landfilling were calculated.…”
Section: Environmental Valuesmentioning
confidence: 99%